Toleransi Beragama Gus Miftah di Gereja Bethel Indonesia (GBI): Analisis Semiotika Charles Sanders Peirce - Prasongko, Wahyu Agung; Fadli, Syairil; Nurliana, Nurliana (Sekolah Ilmu Dakwah dan Komunikasi Islam (STIDKI) Ar Rahmah, 2023)
People in Indonesia have tolerance. Even not all of them can build and implement it. One of Ustadz that can build and implement the tolerance is Gus Miftah. There was a video when he conveyed national oration in official announcement of Indonesia Bethel Church (GBI) Amanat Agung Jakarta Utara. Basically that oration contained representation of tolerance religion value, but there were some bad responses about it, even they said He was an unbeliever by some people. That video became viral after uploaded in Youtube and Instagram. About that video, representation of tolerance religion interested to be researched. Research objectives are to know the representation of religion tolerance on national oration by Gus Miftah in GBI Amanat agung Jakarta Utara official announcement. This research was qualitative and used descriptive approach and semiotic analysis method. There were two data sources in this research, primary and secondary data source. Data collection techniques were observation and documentation. While, data analysis technique used model semiotic by Charles Sanders Peirce. Then for data validation technique used to increase perseverance and peer discussion. The results showed that representation of religion tolerance that appeared in that oration contained element and principle to admit other people right, respect other people belief, agree in disagreement, understand each other, and religious freedom.